Quercetin reduces obesity-induced hepatosteatosis by enhancing mitochondrial oxidative metabolism via heme oxygenase-1. Issue 1 (December 2015) - Kim, Chu-Sook; Kwon, Yoonhee; Choe, Suck-Young; Hong, Sun-Myung; Yoo, Hoon; Goto, Tsuyoshi; Kawada, Teruo; Choi, Hye-Seon; Joe, Yeonsoo; Chung, Hun; Yu, Rina
Abstract Background Obesity-induced hepatic lipid accumulation causes lipotoxicity, mitochondrial dysfunction, oxidative stress, and insulin resistance, and is implicated in non-alcoholic hepatic pathologies such as steatohepatitis and fibrosis. Heme oxygenase-1 (HO-1), an important antioxidant enzyme catalyzing the rate-limiting step in heme degradation, protects against oxidative stress, inflammation, and metabolic dysregulation. Here, we demonstrate that the phytochemical, quercetin, a natural polyphenol flavonoid, protects against hepatic steatosis in obese mice fed a high-fat diet, and that it does so by inducing HO-1 and stimulating increased hepatic mitochondrial oxidative metabolism. Methods Male C57BL/6 mice were fed a regular diet (RD), a high-fat diet (HFD), and an HFD supplemented with quercetin for 9 weeks. Levels of mitochondrial biogenesis and oxidative metabolic transcripts/proteins were measured by real-time PCR and/or Western blotting. HO-1 transcripts/proteins were measured real-time PCR and/or Western blotting. Results Quercetin upregulated genes involved in mitochondrial biogenesis and oxidative metabolism in lipid-laden hepatocytes and the livers of HFD-fed obese mice, and this was accompanied by increased levels of the transcription factor, nuclear erythroid 2-related factor 2 (Nrf-2), and HO-1 protein. The HO-1 inducer hemin and the HO-1 byproduct carbon monoxide (CO) also enhanced hepatic oxidative metabolism in HFD-fed obese mice. Moreover, the metabolic changes and the lipid-lowering effects of quercetin were completely blocked by the HO-1 inhibitor ZnPP and by deficiency of Nrf-2. Conclusion These findings suggest that quercetin stimulates hepatic mitochondrial oxidative metabolism by inducing HO-1 via the Nrf-2 pathway. Quercetin may be useful in protecting against obesity-induced hepatosteatosis.